Hubungan Kualitas Tidur dengan Kontrol Glikemik pada Penderita Diabetes Melitus : Systematic Review - Ulfa Nur Azizah; Moh Arie Wurjanto; Nissa Kusariana; Henry Setyawan Susanto (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: People with Diabetes Mellitus often wake up at night to urinate, thereby reducing the quality of sleep. Sleep quality is related to HbA1c levels. There are many studies regarding the relationship between sleep quality and glycemic control with the results that there is a relationship or no relationship.Methods: This study uses the Systematic Review method with PRISMA guidelines without meta-analysis. Databases used: ScienceDirect, PubMed, Scopus and Portal Garuda. The selected articles were critically assessed with Joanna Briggs Institute questionnaire.Result: There were 17 articles deserved to be analyzed. Many studies state that there is a relationship between global PSQI scores and sleep duration with HbA1c. PSQI is a predictor of HbA1c. The relationship between sleep duration and HbA1c is U-shaped.Conclusion : This study shows that sleep quality is related to glycemic control.